2013
DOI: 10.1371/journal.pone.0077100
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Retinal Ganglion Cells in a Rhesus Monkey Chronic Hypertensive Glaucoma Model

Abstract: Primary open angle glaucoma (POAG) is a neurodegenerative disease characterized by physiological intraocular hypertension that causes damage to the retinal ganglion cells (RGCs). In the past, RGC damage in POAG was suggested to have been attributed to RGC apoptosis. However, in the present study, we applied a model closer to human POAG through the use of a chronic hypertensive glaucoma model in rhesus monkeys to investigate whether another mode of progressive cell death, autophagy, was activated in the glaucom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 47 publications
(85 reference statements)
1
45
0
1
Order By: Relevance
“…Autophagy was induced in a chronic hypertensive glaucoma model induced by laser photocoagulation in primates (Deng et al, 2013) and increased number of autophagosomes and of autophagy related proteins, LC3II and beclin-1, were detected in soma and dendrites of RGCs from rats subjected to episcleral vein cauterization (Park et al, 2012). In the latter study, pharmacological inhibition of autophagy by 3-MA increased cell survival in the ganglion cell layer suggesting a protective role for autophagy (Park et al, 2012).…”
Section: Endogenous Pro-survival Pathways and Neuroprotectionmentioning
confidence: 86%
“…Autophagy was induced in a chronic hypertensive glaucoma model induced by laser photocoagulation in primates (Deng et al, 2013) and increased number of autophagosomes and of autophagy related proteins, LC3II and beclin-1, were detected in soma and dendrites of RGCs from rats subjected to episcleral vein cauterization (Park et al, 2012). In the latter study, pharmacological inhibition of autophagy by 3-MA increased cell survival in the ganglion cell layer suggesting a protective role for autophagy (Park et al, 2012).…”
Section: Endogenous Pro-survival Pathways and Neuroprotectionmentioning
confidence: 86%
“…Park et al [46,51] reported that the activation of autophagy results in the apoptosis of RGCs in a chronic glaucoma model. Although autophagy and apoptosis can coexist in the same damaged RGC, they do not necessarily overlap and can occur independently [58,92]. Autophagy can occur before neuronal apoptosis in aluminum-insulted astrocytes, a chronic hypertensive glaucoma model, and an optic nerve axotomy mouse model [46,93,94].…”
Section: Cross-talk Between Autophagy and Apoptosismentioning
confidence: 99%
“…Deng and colleagues found that autophagy was activated in a chronic hypertensive glaucoma model induced by laser photocoagulation in rhesus monkeys; the enhanced autophagic flux was demonstrated by the increase of LC3II, LC3II/LC3I ratio, and beclin-1 together with the accumulation of autophagic vacuoles and the upregulation of lysosomal activity (Deng et al, 2013). Similarly, Kitaoka and coauthors observed the presence of autophagic vacuoles in unmyelinated axons 3 weeks after IOP elevation induced by laser photocoagulation in rats (Kitaoka et al, 2013).…”
Section: Ocular Hypertensionmentioning
confidence: 92%